The speed-distance relationship for galaxies established by Edwin Hubble - Machado, Daniel Iria (Cadernos de Astronomia, 2024)
The linear relation between the recession velocities of galaxies and their distances or, equivalently, between the redshifts in the spectra of galaxies and their distances, currently known as the Hubble-Lemaître law, is a fundamental result in the area of Cosmology, which can be understood, according to the standard cosmological model, as a consequence of an expanding Universe. In a pioneering work published in 1929, Edwin Hubble (1889-1953) provided consistent evidence for the validity of this law, based on observational data. An English to Portuguese translation of this influential article is presented here.